Confined partial filament eruption and its reformation within a stable magnetic flux rope - Joshi N.C.; Srivastava A.K.; Filippov B.; Kayshap P.; Uddin W.; Chandra R.; Choudhary D.P.; Dwivedi B.N. (My University, 2025)
We present observations of a confined partial eruption of a filament on 2012 August 4, which restores its initial shape within ≈2 hr after eruption. From the Global Oscillation Network Group Hα observations, we find that the filament plasma turns into dynamic motion at around 11:20 UT from the middle part of the filament toward the northwest direction with an average speed of ≈105 km s-1. A little brightening underneath the filament possibly shows the signature of low-altitude reconnection below the filament eruptive part. In Solar Dynamics Observatory/Atmospheric Imaging Assembly 171 Å images, we observe an activation of right-handed helically twisted magnetic flux rope that contains the filament material and confines it during its dynamical motion. The motion of cool filament plasma stops after traveling a distance of ≈215 Mm toward the northwest from the point of eruption. The plasma moves partly toward the right foot point of the flux rope, while most of the plasma returns after 12:20 UT toward the left foot point with an average speed of ≈60 km s-1 to reform the filament within the same stable magnetic structure. On the basis of the filament internal fine structure and its position relative to the photospheric magnetic fields, we find filament chirality to be sinistral, while the activated enveloping flux rope shows a clear right-handed twist. Thus, this dynamic event is an apparent example of one-to-one correspondence between the filament chirality (sinistral) and the enveloping flux rope helicity (positive). From the coronal magnetic field decay index, n, calculation near the flux rope axis, it is evident that the whole filament axis lies within the domain of stability (i.e., n < 1), which provides the filament stability despite strong disturbances at its eastern foot point. © 2014. The American Astronomical Society. All rights reserved.